School-Community Relationships as a Key Factor in the 21st- Century Learning - Umalihayati Umalihayati (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
The study is qualitative design with the study library method. The study aims to explain the idea and benefits of school-community relationships as critical factors for learning in the 21st-Century. The data collection technique started with reading various sources, classifying the data, and analyzing the data. The data are eight articles with Scopus index published from 2017 until 2022 that were collected from reputable journals. The data analysis stated that a harmonious and committed relationship between school and community is a crucial factor in the 21st-Century learning since it influences students’ academic achievement, behavior, and identity. The finding also notifies that the mutual relationship helps schools identify critical issues. To create the relationship, the principal, both top and upper levels, should manage it through intimate communication and interaction with the community through collaboration, running programs from a simple to a broader context.